Tumor‐Associated Lactic Acidosis and Early Death in Patients With Lymphoma - Bahaa Atamna; Alon Rozental; Mohammad Haj Yahia; Gilad Itchaki; Ronit Gurion; Moshe Yeshurun; Pia Raanani; Ofir Wolach (Cancer Medicine)
ABSTRACT Background Cancer is characterized by accelerated glycolysis with enhanced glucose uptake and lactate production, a phenomenon termed Warburg effect (WE). We studied the incidence and clinical impact of Warburg‐driven lactic acidosis in lymphoma. Methods Patients admitted with newly diagnosed or relapsed/refractory lymphoma and documented lactate levels during the first week of admission were included. Patients with lactatemia were classified as secondary (with a recognizable cause for elevated lactate) or none (WE group). Results WE and secondary lactatemia were documented in 58 and 44 patients (15% and 12% of evaluable patients, respectively). Both WE and secondary lactatemia were associated with poor short‐term survival. WE at presentation correlated with tumor burden, with most patients having aggressive disease, advanced stage, and extranodal involvement. WE was associated with high rates of early death (26% and 43% at 30‐ and 60‐days, respectively). Higher lactate levels correlated with worse survival. Earlier initiation of chemotherapy was associated with a (nonsignificant) trend toward better outcomes, whereas steroid and/or thiamine therapy did not alter patient outcomes. Glucose administration was associated with worse survival. Conclusion WE‐driven lactatemia is associated with high tumor burden and increased short‐term mortality in lymphoma. Prompt initiation of anti‐lymphoma therapy may improve outcomes.